PENGARUH PENERAPAN METODE MIND MAPPING TERHADAP DAYA INGAT SISWA DALAM MATA PELAJARAN FIKIH DI MTsN 5 PASAMAN BARAT - Yulia Safitri; Hamdi Abdul Karim, Wedra Aprison, Khairuddin (CV. ADIBA ASIHA AMIRA, 2024)
This research is motivated bythe low memory of some students when students are asked to repeat the material given the previous week, many are still fumbling. Then the results of observations found that the majority of students paid little attention when the teacher taught, indicating a lack of interest and understanding in fiqh lessons. Student learning outcomes scores are still below the minimum completeness criteria. The aim of this research is to determine whether the mind mapping learning method in fiqh subjects has a significant influence on students' memory at MTsN 5 West Pasaman regarding the material on halal and haram food provisions. This research is a quantitative research, the research design used isQuasi Experiment. The sample for this research was class VIII students at MTsN 5 West Pasaman with a sample size of 58 students. The research sample is class VIII. C experiment using the mind mapping method and class VIII. A control with conventional methods. The data analysis technique uses the Normality Test with the Shapiro Wilk formula, and the homogeneity test with the Fisher test followed by hypothesis testing with the paired sample t test. The research results show that based on the results of data processing it can be concluded that there is a significant influence on the application of the mind mapping method as these results prove that the value of the experimental class Sig. (2-tailed) = 0.000 While research alpha = 5% or 0.05. This means that the Sig value. (2-tailed) is smaller than the alpha value (0.000<0.05) so that Ho is rejected and Ha is accepted, meaning that there is an influence of the mind mapping method on students' memory in the MTsN 5 West Pasaman fiqh class VIII material on halal and haram food provisions